Stability assessment, Avayalik Island Cluster, Labrador, Canada, 800-1000 CE - Susan A Kaplan (Arctic Data Center, 2018)
This RAPID award funded two weeks of fieldwork in northern Labrador, Canada. Parks Canada provided Kaplan the vessel, its crew, and polar bear monitors free of charge to accomplish the project. The goal of the fieldwork was to assess the stability of a Middle Dorset (800 CE to 1,000 CE; CE meaning Common Era or the equivalent of 1,216 years ago to 1,016 years ago as of the present date: 2016 CE) archaeological site (Avayalik-1, House 1), located on an outer island 25 miles south of the tip of Labrador. Researchers investigated the vulnerability of Avayalik-1 to rising sea levels and the thawing of permafrost, with the intention of contributing to discussions on how to assess, monitor, and preserve such sites. This information is of great interest to the scientific community, culture resource managers, and also to the indigenous residents who are in many cases the decedents of the original occupants. Avayalik-1, House 1 is a scientifically unique Middle Dorset site. It was last investigated in 1978, and yielded organic artifacts and faunal remains unsurpassed in quantity and preservation by any other Labrador Middle Dorset sites due to the fact the cultural deposits were permanently frozen. However, given the current warming of the Arctic and the rapid thawing of permafrost, many Arctic heritage sites thought for decades to be safe while in the frozen ground are under threat. Avayalik-1 is such a site. A team of three archaeologists conducted foot surveys of the island daily for a week and found evidence of melting permafrost and coastal erosion in many locations. We observed that structures on the main terrace on which Avayalik-1 is located are eroding downslope, particularly those on the southwestern and eastern sides of the main terrace. We closely examined a small cove southwest of Avayalik-1, House 1 and found Ramah chert debitage and Paleoeskimo tools eroding out of the sods and tumbling onto the cove floor, a result of storm surges, loss of permafrost, and water runoff. The artifacts appear to be coming from a structure we labeled Avayalik-1, House 5, perched on the cove's northern edge. While examining these erosion fronts as well as the terrace we observed the following processes at work. Water from thawing permafrost is pooling in some sections of the terrace, while in others it is running downslope from under the turf and sodded areas. The sods at the edges of the main terrace on which Avayalik-1 is located have dried out and there is evidence of earlier sods having tumbled down the terrace face. Any organic remains that had been in these sods have decomposed, but the lithic debitage and tools have endured. As a result, the terrace edges and slopes are littered with worked Ramah chert. While the excavated area of Avayalik-1, House-1 is not near the terrace edge, its cultural deposits are drying out. A small portion of unit 4N/8E in Avayalik-1, House 1 was excavated using trowels and revealed that the house deposits still have much to yield. Despite the fact that the deposits are no longer frozen, artifacts including spun cordage, knotted baleen, an ivory pin, baleen strips, hide and fur fragments, as well as marine mammal and bird bones were recovered. Wood was encountered, but it was not in good shape, which is not surprising, since archaeologists working on thawing middens in Greenland have documented that wood is one of the first types of organic materials to be lost. Bulk soil samples collected every 10 cm were processed and revealed that botanical and entomological remains have been preserved in the deepest site deposits. Charcoal and wood samples were recovered from various stratigraphic levels, offering the possibility that we can generate a more detailed chronology of the 60 cm of Middle Dorset deposits. Other than the soil samples, these collections have yet to be analyzed due to delays securing permits to move the marine mammal material across the Canadian-USA border. The 2016 team located six suspected buried house structures at Avayalik-1, in the vicinity of House 1. Two were tested and frozen deposits were encountered in both test pits. We believe that other structures likely contain frozen deposits as well. Two of those features, Houses 5 and 6, are in danger as they are adjacent to the actively eroding front of the small southwestern cove discussed above. Despite the loss of a total of five days to weather delays, researchers accomplished everything they set out to do. They determined that important structures and cultural deposits on the island are in danger due to the thawing of permafrost and coastal erosion. They recovered wood and charcoal that will hopefully provide a more refined set of dates of the Avayalik-1, House 1 Middle Dorset deposits, got a good sense of the state of preservation of those deposits, and identified additional structures that should help shed light on Middle and Late Dorset use of the island. In addition, they collected samples and artifacts that in the coming months will be analyzed using various archaeometric techniques. Hopefully the analyses will provide additional insights into the cultural and environmental history of the island. The dataset contains specific archaeology site locations, photographs, fieldnotes, and an archaeology collection inventory. The information is being used to assess the stability of Avayalik-1, a Paleoeskimo site of importance to understanding the prehistory of Labrador, Canada. According to the terms of the research permit, the data collected must be deposited with Parks Canada, the archaeology office of the Province of Labrador-Newfoundland, and Nunatsiavut Archaeology Office. The data can be accessed through those repositories only, for Canada considers exact locations and the contents of archaeological sites protected information. Once the collections are across the border and analyzed they will be published and the data deposited with the approved repositories.